2014
DOI: 10.1111/clr.12510
|View full text |Cite
|
Sign up to set email alerts
|

Post‐extraction evaluation of sockets with one plate loss – a microtomographic and histological study

Abstract: Long-term analysis showed that plate loss interfered in final ridge measurements by reducing the middle portion of the socket width compared to the intact plate sockets. The histological and micro-CT qualitative analysis showed that both sites presented similar pattern of healing, despite the reduced dimension found in plate loss sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In an experimental study in eight rabbits the buccal wall of the alveolus was deliberately removed in half or the sites (experimental group) and left intact in the control group. 26 Micro CT analysis showed decreased amounts of bone width in the experimental group in the previous socket area.…”
Section: Trauma From Tooth Extractionmentioning
confidence: 83%
See 1 more Smart Citation
“…In an experimental study in eight rabbits the buccal wall of the alveolus was deliberately removed in half or the sites (experimental group) and left intact in the control group. 26 Micro CT analysis showed decreased amounts of bone width in the experimental group in the previous socket area.…”
Section: Trauma From Tooth Extractionmentioning
confidence: 83%
“…The investigators concluded that this disturbed wound healing will eventually lead to lower amounts of bone volume in the area of the previous extraction socket. In an experimental study in eight rabbits the buccal wall of the alveolus was deliberately removed in half or the sites (experimental group) and left intact in the control group . Micro CT analysis showed decreased amounts of bone width in the experimental group in the previous socket area.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…This divulsion extended ≈3 mm apically to margins of peri‐implant dehiscence, enabling graft placement in the peri‐implant gap to fill the dehiscence. At bone margins adjacent to the defect, graft stabilization conditions were obtained and the attached and stable mucoperiosteal tissue surrounding the defect prevented displacement of the biomaterial 18 . The anatomic scenario in Class II dehiscence defects, in which volume stability is achieved by the adjacent bone walls in combination with an implant placed within confines of the bony defect, facilitates use of this technique 17 , 23 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Such studies have evaluated extraction sockets and immediate implants at sites with intact bone walls, but little is known with regard to sockets that feature buccal bone loss. In an animal model study, it was observed that healing of buccal bone defects after extraction had a distinctive pattern when compared with sockets with intact walls, where the former showed greater dimension loss 18 …”
mentioning
confidence: 99%
See 1 more Smart Citation